Pain treatment at the C.B.P. - Bzurovski, Enrique (Cirugía del Uruguay, 1982)
Pain is a frequent sympton often persistent and difficult to treat. It is caused by mediastinal or thoracic wall invasion where the Pancoast tumor is pointed out. The different pathogenic mechanisms are studied. When selecting the correct treatment the needs of working in a multidiscipline group is emphazised. A reasonable use of analgesic drugs is adviced as well as the ideal analgesic is defined. A progressive plan is suggested starting from very mild drugs to the very strong ones, trying to obtain the maximum benefits offered by each product. At the begining ASS will be administrated and it could be combined with paracetamol or codeine. The next step is the prescription of sinthetic morfinomimetics: D-propoxifeno (Dioxadol) or Pentazocima (sosegón). If pain relief is not obtained, then these drugs will be substituted by narcotics. The disadvantages of the parenteral usage of these drugs are stressed. The good results obtained with the morphine products for oral intake are emphazised. The different types and indications of nervous blockade is exposed. The advancements in pain relief are considerable and. one of them are the neurostimulators of very re centusage.